Financing for development : issues in domestic public resource mobilization and international development cooperation : executive summary (UN New YorkUS, 2017)
Summarises core issues in the areas of domestic public resource mobilisation and international development cooperation, as discussed in the Addis Ababa Action Agenda of the Third International Conference on Financing for Development. Provides overviews of the main challenges that developing countries face in these areas.
Note by the UNCTAD Secretariat.